Assessment of sociodemographic and psychiatric characteristics of transgender adults seen at a Midwest tertiary medical center - Cortez, Samuel; Moog, Dominic; Baranski, Elizabeth; Williams, Kelley; Wang, Jinli; Nicol, Ginger; Baranski, Thomas; Herrick, Cynthia J. (Frontiers in Endocrinology, 2024)
Background: The National Academy of Medicine has formally identified transgender adults as an understudied population in critical need of health research. While national surveys, like the US Transgender survey, have characterized higher rates of depression, anxiety, suicidality and socioeconomic need in the transgender community, studies have not examined the impact of sociodemographic and clinical characteristics on mental health related outcomes.To describe the sociodemographic and mental health characteristics of transgender adults seen at a large Midwest transgender clinic and to determine factors associated with self-reported mental health conditions. Methods: Descriptive, retrospective, cross-sectional study of new transgender patients 18 years and older seen at a large Midwest transgender clinic between December 2019 and June 2022.Results: A total of 482 charts were reviewed. During their initial evaluation, 11.6% (56/482) reported having a history of suicide attempt and 81.30% (392/482) reported a mental health diagnosis with the most common being depression, anxiety, attention deficit disorder, and posttraumatic stress disorder. Multivariable logistic regression results show no single factor was significantly associated with mental health diagnosis after adjusting for the effect of age and race.Patients who were new to gender affirming hormone therapy (54%, 254/468) are 2.0 (95% CI 1.4-2.9) times more likely to report having a mental health care provider than patients who were seen for continuation of therapy (46%, 214/468). Ten records with race not disclosed, 3 records with gender identity "other" and 2 records with gender identity not disclosed were excluded from analysis.Conclusion: This study reinforces the finding that transgender adults have an increased lifetime prevalence of mental health conditions. The higher prevalence of mental health conditions in our clinic was not associated with sociodemographic factors included in the study. Furthermore, transgender patients are less likely to have seen mental healthcare providers after initiation of GAHTgender affirming hormone therapy.